2021
DOI: 10.3389/fpsyg.2021.726150
|View full text |Cite
|
Sign up to set email alerts
|

Meaning Reflectivity in Later Life: The Relationship Between Reflecting on Meaning in Life, Presence and Search for Meaning, and Depressive Symptoms in Older Adults Over the Age of 75

Abstract: Background: Over the last decades, there is growing attention for the importance of meaning in life for older adults. However, there is virtually no insight into the mental processes that contribute to this experience. Some scholars recently called for an investigation of meaning reflectivity, or the process of reflecting on issues specifically related to meaning in life. In this study, we explored to what extent older adults talk and think about issues of meaning in life, and how this meaning reflectivity is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Moreover, some researchers have noticed that the search for meaning is more valuable for people in difficult circumstances, such as disease, to the presence of meaning [123]. For example, searching for meaning was higher than the presence of meaning among adults with physical disabilities [124], high health anxiety [57], and chronically ill patients who, based on cluster analysis, showed the features of a poorly adapted group [73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some researchers have noticed that the search for meaning is more valuable for people in difficult circumstances, such as disease, to the presence of meaning [123]. For example, searching for meaning was higher than the presence of meaning among adults with physical disabilities [124], high health anxiety [57], and chronically ill patients who, based on cluster analysis, showed the features of a poorly adapted group [73].…”
Section: Discussionmentioning
confidence: 99%
“…Park et al [72] observed that people with greater meaning, both the presence of and the search for, declare higher levels of life satisfaction and happiness. Several researchers consider meaning in life as a key variable in the framework of positive functioning in different stages of development [73]. Since life satisfaction refers to people's positive evaluation of their life, and happiness also reflects, among other aspects, positivity [68], it can be assumed that meaning in life may be a predictor of positive orientation.…”
Section: Meaning In Life and Positive Orientationmentioning
confidence: 99%
“…Our findings support this idea that positive relationship quality was not associated with caregiver mental health problems whereas negative relationship quality was a significant predictor of mental health problems in both models. Another possible explanation is that people tend to focus on searching for meaning in life as they age (Dewitte & Dezutter, 2021; Filip et al, 2020). Therefore, it is possible that older caregivers view caregiving as a source of personal satisfaction and emotional fulfillment rather than perceiving it as a burden (Peacock et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The significance of purpose in life for older persons has drawn more attention in recent decades. There is, however, hardly any grasp of the mental processes that contribute to this experience (Dewitte & Dezutter, 2021). Humans need a sense of meaning and purpose in their lives.…”
Section: Introduction Background Of the Studymentioning
confidence: 99%
“…Beyond the losses associated with aging, Tornstam has been reframing and broadening our understanding of the experience of aging, pointing out that there is still a capacity for learning, growth, and psychological development (Worth & Smith, 2021). Researchers in the study of aging is increasingly describing the psychological sense of life's significance as a vital factor to consider while discussing positive late functioning of life (Dewitte & Dezutter, 2021). While some researchers found retirement to have a good impact on mental health, others reported a negative or insignificant effect on behavior and lifestyle (Bedaso & Han, 2021).…”
Section: Introduction Background Of the Studymentioning
confidence: 99%